« To see beyond the horizon of mere selfishness » : l’horizon moral dans les romans de George Eliot - Benjamine Toussaint (Cahiers Victoriens et Edouardiens)
In spite of her apostasy, George Eliot still believed in the moral and spiritual values of Christianity and it is hardly surprising she should have used the metaphor of the horizon to refer to this ideal notion of the essence of Christianity since the horizon is both unreachable and yet always visible, showing the direction one ought to follow. Her characters’ moral odyssey is about learning to see beyond the limits of their own self-centered experience; however, as Lydgate underlines in Middlemarch, « a man’s mind must be continually expanding and shrinking between the whole human horizon and the horizon of an object-glass. » We shall therefore focus not only on George Eliot’s insistence on the necessity « to see beyond the horizon of mere selfishness » but also on the idea that a genuine moral horizon can only exist in her eyes if people develop the capacity to contemplate various horizons, not only the most distant ones but also those that are the closest to them so that they should not neglect the sufferings of individuals for the sake of abstract ideals. Sight and vision are clearly linked in George Eliot’s novels and so is the notion of sympathy since Lydgate compares the idea of the mind shrinking and expanding with that of « a systole and a diastole » thus implicitly referring to the beating of the heart.